2019
DOI: 10.1111/nicc.12419
|View full text |Cite
|
Sign up to set email alerts
|

Occupational stress, quality of working life and turnover intention amongst nurses

Abstract: Background Turnover intention is a frequent event in almost all institutions and is associated with unfavourable consequences for employees. Aim The aim of this study was to examine the relationship between occupational stress, quality of working life and turnover intention amongst nurses working in critical care units in Iran. Design A cross‐sectional survey design was used. Method The study was conducted in the critical care units of 10 hospitals in Tabriz, Iran, between July and November 2017 using a sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
62
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(75 citation statements)
references
References 49 publications
9
62
0
4
Order By: Relevance
“…Job stress and physical and mental fatigue was previously reported to accompany hospital accreditation [ 29 , 36 , 37 ]. Stress creates physical and mental problems for employees and negatively affects their quality of life [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Job stress and physical and mental fatigue was previously reported to accompany hospital accreditation [ 29 , 36 , 37 ]. Stress creates physical and mental problems for employees and negatively affects their quality of life [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Findings from a study conducted in Saudi Arabia indicated that 52.4% of nurses, particularly primary health care nurses, were dissatisfied with their QWL [ 1 ]. Recent studies in Iran showed that between 70.8 and 81·2% of nurses reported that their QWL was low [ 7 , 10 ]. A recent study in Ethiopia showed that 67.2% of the nurses were dissatisfied with the quality of their work life [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 ] Our earlier study conducted in hospitals in Tabriz also showed high levels of occupational stress among critical care nurses. [ 5 ]…”
Section: Introductionmentioning
confidence: 99%